Promenading in the enchanted realm of Kronecker powers: single monomial probabilistic evolution theory (PREVTH) in evolver dynamics - Demiralp, Metin (Springer Science and Business Media LLC, 2017)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Problems related to evolution; Kronecker product; Kronecker power series; Alternative quantum mechanics (including hidden variables, etc.); Analytical theory of ordinary differential equations: series, transformations, transforms, operational calculus, etc.; probabilistic evolution theory; space extension; telescope matrices; Prevth; PREVTH recursions